Educated by Hitting: Examining Authoritarian Parenting Patterns in the Batak Toba Ethnic Community in the Samosir Area, Ambarita Village - Wilda, Annisa; Diputera, Artha Mahindra; Victoria, Herlina Deborah; Br Siregar, Permata Sari; Sidauruk, Hani Eklesia; Br Sinuraya, Ribka Julianta (UPI Kampus Cibiru, 2023)
This research aims to find out how parenting patterns have developed in the Batak Toba ethnic in the Samosir Region and whether the Toba Batak tribe community in the Samosir Region uses a parenting style that involves hitting (Authoritarian). This research was conducted in Ambarita Village, Simanindo District, Samosir Regency with a population of 400 heads of families. The sample used was 80 parents. This research uses a combination method (Mix method) using a Sequential Explanatory research approach. Data processing techniques are carried out by distributing questionnaires and conducting interviews. Based on the research results, it can be concluded that the parenting pattern applied by the Toba Batak tribe is 85% democratic parenting, parenting patterns authoritarian 15%, permissive parenting is 0%, that is, there are no parents who apply permissive parenting (abandoning the child). 1) parents who do not give freedom to children and restrain children 2) parents who give punishment by hitting or pinching when the child makes a mistake. This research will have an impact on parents in communities who have children to apply parenting patterns that are in accordance with the characteristics of children and provide input and encouragement to children to find the best way to achieve their goals